Pengaruh Tingkat Pendidikan dan Jumlah Penduduk Terhadap Tingkat Kemiskinan di Kota Pekanbaru - Herman . (Universitas PGRI Madiun, 2018)
The purpose of this research is to see the effect of education level and population topoverty level in Pekanbaru city either partially or together. Population in this researchPekanbaru City 2011-2017. The data used in this study is secondary data obtained from theCentral Bureau of Statistics (BPS) Pekanbaru city. While the method of analysis usingmultiple regression analysis techniques. The results showed that the level of education doesnot significantly affect the poor in Pekanbaru City. While the number of residents significanteffect on the poor in Pekanbaru City while simultaneously variable education level and thenumber of residents significantly affect the poor in Pekanbaru City. The magnitude ofinfluence is 94.1 percent.